Кріоекстракт плаценти – перший український біотехнологічний противиразкових засіб (огляд літератури та власних досліджень) - Кошурба, І.В.; Гладких, Ф.В.; Чиж, М.О. (Кошурба ІВ, Гладких ФВ, Чиж МО. Кріоекстракт плаценти – перший український біотехнологічний противиразкових засіб (огляд літератури та власних досліджень). Сучасна медицина, фармація та психологічне здоров’я. 2023; 1 (10): 32–40. DOI: https://doi.org/10.32689/2663-0672-2023-1-4, 2023)
Placenta cryoextract was first obtained by scientists of the Institute of Problems of Cryobiology and Cryomedicine of the National Academy of Sciences of Ukraine, who developed and put into practice a unique method of its longterm storage in a low-temperature environment. It is known that the placenta implements trophic processes and protein synthesis, gas exchange, hormone secretion and hormone regulation, blood pressure maintenance, blood coagulation, antitoxic function and excretion of metabolites, deposition of biologically active substances, immune regulation, regulation of lipid peroxidation processes, etc. The aim of the study was to summarize data from literary sources and the results of own research on the anti-ulcer activity of placenta cryoextract. Materials and methods. The selection of publications was made according to the Scopus, Google Scholar and PubMed databases, which covered information on the anti-ulcer activity of placenta cryoextract and modern information on approaches to the treatment of peptic ulcer disease. Research results and their discussion. Summarization of literature data on experimental studies of the antiulcer activity of placenta cryoextract demonstrated the implementation of a complex program of preclinical studies on nine experimental models of ulcer disease: on the model of alcohol-prednisone ulcer, on the model of stress ulcer, on the model of serotonin-induced ulcer, on the model of chronic acetic acid ulcer, on indomethacin-induced ulcerogenesis model, diclofenac sodium-induced ulceration model, meloxicam-induced ulceration model, ibuprofen-induced ulcerogenesis model, and acetylsalicylic acid-induced ulcerogenesis model. Conclusions. The use of cryoextract of the placenta shows pronounced antiulcer activity both in classic models of peptic ulcer disease (serotonin, alcohol-prednisone, acetic acid, stress) and in models of drug-induced ulcerogenesis – in gastric ulcers induced by nonsteroidal anti-inflammatory drugs. Generalized data from the literature indicate the feasibility of studying the possibility of conducting the first phase of clinical studies of the effectiveness of the use of cryoextract of the placenta as a new domestic antiulcer drug.
PLACENTA CRYOEXTRACT IS THE FIRST UKRAINIAN BIOTECHNOLOGICAL ANTI-ULCER AGENT (REVIEW OF THE LITERATURE AND OWN RESEARCH)
Кошурба ІВ, Гладких ФВ, Чиж МО. Кріоекстракт плаценти – перший український біотехнологічний противиразкових засіб (огляд літератури та власних досліджень). Сучасна медицина, фармація та психологічне здоров’я. 2023; 1 (10): 32–40. DOI: https://doi.org/10.32689/2663-0672-2023-1-4
Keywords: кріоекстракт плаценти